D.light Design : marketing channel strategies in India - Coughlan, Anne T.; Neuwirth, Benjamin ([London] : SAGE, 2016)
This case looks at a new start-up company, d.light Design, as it was seeking to go to market in India with its solar-powered LED lamps in 2009. Sam Goldman, founder and chief customer officer of d.light, was in New Delhi, India; his business-school friend and co-founder Ned Tozun was in China, the site of the company's manufacturing plant.
Originally Published in: Coughlan, A., & Neuwirth, B. (2015). d.light Design: Marketing Channel Strategies in India. 5-214-255. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; d.light Design (Firm); Marketing channels -- Case studies; New products -- Case studies; New business enterprises -- Case studies